Characterization of a novel adeno-associated viral vector with preferential oligodendrocyte tropism - Powell, SK (Gene Ther, 2016)
No adeno-associated virus (AAV) capsid has been described in the literature to exhibit a primary oligodendrocyte tropism when a constitutive promoter drives gene expression, which is a significant barrier for efficient in vivo oligodendrocyte gene transfer. The vast majority of AAV vectors, such as AAV1, 2, 5, 6, 8 or 9, exhibit a dominant neuronal tropism in the central nervous system. However, a novel AAV capsid (Olig001) generated using capsid shuffling and directed evolution was recovered after rat intravenous delivery and subsequent capsid clone rescue, which exhibited a > 95% tropism for striatal oligodendrocytes after rat intracranial infusion where a constitutive promoter drove gene expression. Olig001 contains a chimeric mixture of AAV1, 2, 6, 8 and 9, but unlike these parental serotypes after intravenous administration Olig001 has very low affinity for peripheral organs, especially the liver. Furthermore, in mixed glial cell cultures, Olig001 exhibits a 9-fold greater binding when compared with AAV8. This novel oligodendrocyte-preferring AAV vector exhibits characteristics that are a marked departure from previously described AAV serotypes.